Сюлэм гуртэ дыртэ: веросъес, повестьес, кылбуръес / В. В. Котков - Котков Владимир Васильевич (Удмуртия, 2019)
Экземпляры: КО (2019) / Инвентарный номер: 55619 / Цена: / Сис.шифр: К84(2Рос.Удм) / Авт.знак: К 73 / ГРНТИ: 17.82.30 / ББК: 84(=664.1)